Dynamic Relationship Between Air-Rrailways Transportation and Economic Growth in Pakistan: Evidence from Robust Least Squares Regression Estimator (Journal of Asian Development Studies, 2020)
The objective of the study is to examine the dynamic linkages between air-railways transportation and Pakistan’s economic growth under Asian and Global financial crisis. The study selected a time period from 1980-2016 for robust inferences. The results confirmed the inverted U-shaped relationship between air transportation and economic growth while monotonic decreasing relationship found between railways transportation and country’s economic growth. The result implies that air-railways transportation perform in a limited capacity that not contributed in optimized way to generate sufficient income in service value added for a country. The Asian and Global financial crisis, however, not confined its significant impact on Pakistan’s transportation sector.  The study emphasized the need of re-corrective measures to promote air-railways transportation with improve service quality dimensions, reduced complex networking, less freight charges, reduced long-queued booking schedules, comfortable seats, good working environment, provide technical and financial assistance, etc., these measures would helpful to improve Pakistan’s transportation sector in order to contribute in country’s development projects. The study has a no vel contribution in the existing literature by including Asian and global financial crisis in air-railways transportation that translated into country’s economic growth. Further, the non-linear relationship was found between country’s per capita income and air-railways transportation to verify either of the three alternatives and plausible hypothesis, i.e., inverted U-shaped relationship, U-shaped relationship, and/or flat relationship between them. We believe that this study is first in its kind, as per authors knowledge, which included financial crisis in transportation modeling to proposed robust policy inferences in a given country context.